Eutanasia e CoViD-19. Perché l’espansione della pandemia del secolo richiede un’urgente riflessione in merito ad eutanasia ed assistenza al suicidio (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The CoViD-19 pandemic has shocked the Italian health system forcing physicians to define criteria for the admission or exclusion of patients to intensive care treatments, in case of a disproportion between the health resources available and those deemed necessary. At the same time with the judgment n. 242/2019 the Italian Constitutional Court ruled out the responsibility, under specified conditions, for assisted suicide, admitting a legislation that allows this kind of practice. The thought that a high number of people could be deprived of the necessary healthcare due to lack of resources, urges the Italian State to discipline euthanasia and assisted suicide in order to offer patients – if not the protection of their right to health – at least the protection of their own dignity and freedom.
Keywords: CoViD-19; pandemic emergency; euthanasia; assisted suicide; intensive care